Breast image analysis for risk assessment, detection, diagnosis, and treatment of cancer - Giger, Maryellen L.; Karssemeijer, Nico; Schnabel, Julia A. (2013)
The role of breast image analysis in radiologists' interpretation tasks in cancer risk assessment, detection, diagnosis, and treatment continues to expand. Breast image analysis methods include segmentation, feature extraction techniques, classifier design, biomechanical modeling, image registration, motion correction, and rigorous methods of evaluation. We present a review of the current status of these task-based image analysis methods, which are being developed for the various image acquisition modalities of mammography, tomosynthesis, computed tomography, ultrasound, and magnetic resonance imaging. Depending on the task, image-based biomarkers from such quantitative image analysis may include morphological, textural, and kinetic characteristics and may depend on accurate modeling and registration of the breast images. We conclude with a discussion of future directions. Copyright © 2013 by Annual Reviews.
CRIS-Team Scopus Importer:2023-03-08
Keywords: biomechanical modeling; breast cancer; classification; computer-aided detection; computer-aided diagnosis; image processing; image registration; medical imaging; risk assessment